Self, Culture, and Others in Womanist Practical Theology. - Sheppard, Phillis Isabella (Black religion/womanist thought/social justice, 2011)
To illustrate the complexities of black women's experiences of self-identification and racial embodiment, Phillis Isabella Sheppard provides an account that engages both psychoanalytic theory and the role of religion and cultural objects in self-understanding.